Examining self-efficacy levels of football referees - Sercan Kural; Faruk Aydin (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: This study examined football referees' self-efficacy in relation to multiple variables. In this context, the aim of the research is to examine the self-efficacy of football referees according to various variables. Material and Methods: The sample included 278 football referees (Meanage=26.00 ± 5.72 years) from different classes in Ankara province. Participants, selected by convenience sampling, completed the Referee Self-Efficacy Scale (REFS). After testing the main assumptions of parametric tests, t-tests and one-way analysis of variance (ANOVA) were used for data analysis. Results: The t-tests revealed no significant difference in gender and education. As for the ANOVA results, there were significant differences in REFS dimensions "physical competency," "game knowledge," and "decision-making" in age; "game knowledge" and "decision-making" in income; and "physical competency" and "decision-making" in refereeing level. Conclusion: Self-efficacy levels of football referees vary according to refereeing categories, income levels, and age.